UNTAMED AND DISCIPLINED: CONTEXTUAL ICONOGRAPHY AND THE TRANSFORMATION FROM VINĀYAKA TO GAṆEŚA IN EARLY SOUTH ASIAN SCULPTURE - Jawdekar, Ketan (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This research paper re-examines the iconography of Gaṇeśa through a contextual and interdisciplinary framework that integrates textual traditions, archaeological materials, and theories of embodied cognition. Rather than viewing Gaṇeśa solely as a mythological figure, the study investigates how elephant and nāga symbolism, early Vināyaka imagery, and visualisation practices contributed to the development of a stabilised sculptural form. Drawing on examples from the earliest iconographical representations, the paper proposes a contextual methodology for decoding iconography, in which narrative setting, sculptural placement and artistic strategies shape meaning. Particular attention is given to visual narratives depicting the negotiation between untamed and disciplined states of awareness. By analysing attributes such as the pāśa and aṅkuśa alongside narrative motifs of obstruction and transformation, the study suggests that Gaṇeśa’s form reflects an evolving dialogue between scriptural metaphors and artistic practice. The study contributes to South Asian iconographic scholarship by demonstrating how sacred imagery operates as a relational visual language grounded in material culture rather than fixed symbolic interpretation.